Incidentally detected solid pseudopapillary neoplasm of pancreas in a child with an ovarian cyst: a case report - Reddy, Sandeep M.; Prasad, Siva K.; B., Shilpa; G., Baleswari (International Journal of Research in Medical Sciences, 2020)
Solid pseudopapillary neoplasms (SPN) are the most common as well as very rare pediatric tumors of the pancreas. Most of the literature is derived from adult SPNs. As per world health organization, these tumors considered as low grade malignant with excellent survival outcomes after complete surgical resection. We report a case of incidentally detected SPN in a 16-year-old female child with an ovarian cyst. She underwent pylorus preserving pancreaticoduodenectomy and ovarian cystectomy. Histopathology revealed well differentiated SPN of the pancreas head and ovarian cystadenoma. She is symptom-free at the 6th month follow up.